Oral history interview with Sidney Morris, March 18, 2004 - Morris, Sidney (Valdosta State University Archives and Special Collections, 2004)
Oral history interview with Sidney Morris, March 18, 2004. Valdosta (Ga.). Fieldworker: Gregory Barlow. Audio file digitized from cassette tape. Part of the South Georgia Folklife Project at Valdosta State University Archives and Special Collections. The contents are an analysis of Morris’s life as a Jew in Valdosta. The interview focuses on several aspects of Jewish life in the area, predominantly how Southern and Jewish traditions influence each other.
1 electronic record(s) and derivatives. 1 audio file (wav, mp3) 298,924,788 bytes. 00:36:13. 3 PDF documents (8 scans, jp2). Approx. 633 MB (664,362,495 bytes).
Keywords: Georgia; Oral histories; Sound recordings; Jews; Judaism--Customs and practices; Valdosta (Ga.)